Administrative law in a changing state : essays in honour of Mark Aronson - Aronson, Mark (Mark I.); Pearson, Linda; Taggart, Michael; Harlow, Carol (Hart Pub., 2008)
This book of essays celebrates Mark Aronson's contribution to administrative law. As joint author of the leading Australian text on judicial review of administrative action, Aronson's work is well-known to public lawyers throughout the common law world an.